Sintesis Carboxymethyl Konjac-Glucomannan (CM-KGM) dari Tepung Porang: Pengaruh Media dan Suhu Karboksimetilasi terhadap Nilai Derajat Substitusi - Sperisa Distantina; Amellia Setyani Putrie; Inas Novianti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
To increase the solubility of porang flour or konjac flour, the konjac flour was modified chemically into carboxymethylation konjac-glucomannan (CM-KGM). CM-KGM was prepared by alkalization of konjac flour using sodium hydroxide for 30 minutes at 30oC. After then, product alkalization was carboxymeted using sodium monochloroacetic (Na-MCA) with ratio 1:1 gram flour/NA-MCA. The aims of this research were to study the effect of concentration ethanol as the solvent media (50% ethanol and 90% ethanol) and temperature (45-50oC dan 65-70oC) to the rate of degrees of substitution (DS) formation in carboxymethylation step. Based on the data, the highest DS was attained by carboxymethylation using media solvent 90% ethanol, time of carboxymethylation 150 minute and temperature carboxymethylation 45-50C. The relationship between temperature and reaction constant (k) follows      k = 0,3082 exp (-15.227,8064/8,314T )